2014
DOI: 10.14233/ajchem.2014.15956
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Some Substituted Heterocyclic Fluconazole Analogues as Antifungal Agents

Abstract: During the past few decades, fungal infections are the commonly prevalent diseases from which a large proportion of the human population suffers 1-5. The increased emergence of both the superficial and systemic fungal infections has led to the massive increase in the rate of mortality, especially in the immuno-compromised individuals, those suffering from tuberculosis, cancer or AIDS 6,7. In clinic, azoles, especially triazole antifungal agents, were used most widely and efficiently. For example, fluconazole, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Organo-bentonite, GK-4, was purchased from Jiangxi Gukang new materials Co. Ltd. Nano-magnesium hydroxide with average length of 193.9 nm and specific surface area of 22.4 m 2 /g was prepared using hydrothermal treatment 34 . Polypropylene, T30R, was supplied by Qilu Petrochemical Co. Ltd.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organo-bentonite, GK-4, was purchased from Jiangxi Gukang new materials Co. Ltd. Nano-magnesium hydroxide with average length of 193.9 nm and specific surface area of 22.4 m 2 /g was prepared using hydrothermal treatment 34 . Polypropylene, T30R, was supplied by Qilu Petrochemical Co. Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…2 and Table-4 that, despite the initial decomposition temperature of S1 or S2 is slightly lower than that of S0, when the temperature exceeds 400 ºC, the mass loss of S1 or S2 is less than that of S0 at the same temperature. The purity magnesium hydroxide completely decomposes at 400 ºC for the magnesium oxide 34 . It can be found that, although the thermal stability of magnesium hydroxide is lower than that of polypropylene, the addition of magnesium hydroxide especially BT/MH improves the thermal stability of polypropylene, which further confirm the flame retardant synergism of bentonite and magnesium hydroxide in polypropylene.…”
Section: Flammability Characterization By Horizontal Burning Testmentioning
confidence: 99%
“…An alternative strategy to increase the number of molecules in a chemical library from CuAAC reaction consists in changing the azide-alkyne group position on the reactive sites. With this idea, diverse alkynes were treated with 1-Azido-2-(2,4difluoro-phenyl)-3- [1,2,4]triazol-1-yl-propan-2-ol (9) yielding fluconazole analogues of type 10 [22][23][24]. All the compounds were highly active against different strains of fungi which prove that this kind of molecules possess an activity similar or higher than fluconazole having as further benefit that synthesis of these compounds is carried out with fewer reactions compared to the commercially available compound.…”
Section: Introductionmentioning
confidence: 99%